Set and spike - Lawrence, David; Yu, Bill (Get in the game (Magic Wagon (Firm)), 2019)
Award-winning volleyball player Lucy Andia tries out for the Peabody team, certain she will be the star player. However, Lucy finds out there are other girls with greater talent, and Lucy is finding it hard to embrace her new role on the team.